PENGARUH MODEL EXAMPLES NON EXAMPLES PADA PEMBELAJARAN PKn TERHADAP HASIL BELAJAR SISWA KELAS III - Fitria Ulfa; Asmayani Salimi; Suhardi Marli (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis study aimd to analyze the effect of using the examples non examples model on student learning outcomes in learning citizenship education 3th grade students of  public elementary 38 school in northern pontianak. The method used was the experimental method, the form of research used was quasi experimental design with the design of nonequivalent control group design. The population and sample in this study were all 3th grade students of  Public Elementary 38 School in Northern Pontianak.. Based on data analysis, the average post-test results of the experimental class were 86,57 while the average post-test results of the control class 79,43. The results of the t test obtained tcount of 3,404 and ttable α = 5% (with dk = 29 + 29 - 2 = 56 )is 3,404 ,which means  tcount (3,404)> ttable (2,0042), then Ha is accepted. It was concluded that there is a  effect of using the examples non examples model student learning outcomes in learning citizenship education 3th grade students of  public elementary 38 school in northern pontianak. From the results of ES calculations, obtained ES for 0,88 (high criteria). This means using the examples non examples model give a good effect on student learning outcomesin learning citizenship education 3th grade students of  public elementary 38 school in northern Pontianak..Keywords: Examples Non Examples, Influence, Learning Outcomes